Perlindungan Hukum terhadap Nasabah atas Hilangnya Jaminan Kredit pada Lembaga Perbankan di Indonesia - Shelly Asrika Fazlia; Muskibah Muskibah; Muhammad Amin Qodri (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to analyze the regulation of legal protection for customers regarding the loss of credit collateral in banking institutions in Indonesia and the legal implications arising from the credit agreement between customers and banks. The results of the study indicate that the regulation of legal protection for customers in the event of the loss of credit collateral has not been explicitly regulated in Indonesian legislation. Law Number 10 of 1998 concerning Banking places greater emphasis on protecting depositors compared to debtor customers, while the Deposit Insurance Corporation only guarantees customer deposits and does not cover credit collateral. Consequently, when the loss of credit collateral occurs, dispute resolution often depends on judicial interpretation by applying general provisions of the Civil Code such as breach of contract and unlawful acts. The legal implications of the loss of credit collateral by banks indicate that banks may be held liable under civil, administrative, and even criminal law if the loss occurs due to negligence. The loss of collateral documents constitutes a violation of the prudential principle in banking activities and may result in the obligation for banks to compensate customers for the losses incurred. Therefore, regulatory reform is necessary to establish clearer and more comprehensive provisions regarding bank liability, mechanisms for replacing lost collateral documents, and forms of legal protection for customers in order to ensure legal certainty in credit agreement relationships.